АВТОМАТИЗОВАНИЙ ПРИСТРІЙ ДЛЯ КОНТРОЛЮ ОСЕРДЯ СТАТОРА ПОТУЖНОГО ТУРБОГЕНЕРАТОРА - Левицький, А.С.; Зайцев, Є.О.; Панчик, М.В. (Інститут електродинаміки НАН України, Київ, 2021)
A device for automated control by the stator core of a powerful turbine generator (TG) during assembly and pressing at the manufacturing plant is proposed. Using the device, places in the core with a weakened solidity are determined. For this, at N points evenly spaced along the cross section of the stator core, the specific pressing pressure of special plastic elements, which are installed in the control cells of the additional pressure ring of the press, on which the core is assembled, is measured. During pressing, the elements are deformed, and their deformation depends on the degree of core defect (decrease in solidity) in the zone of which they are located. The sample will be deformed less, located in the zone of the largest defect, and most of all - in the zone where the defect is minimal. The pressure is measured using a flat metal membrane with a rigid center on which strain gauges are located at selected points. It is shown that the relative deformations in a flat membrane, which are measured by strain gages, depend on the value of the specific pressing pressure. Analytical relationships between the relative radial and tangential deformations and the specific pressing pressure have been determined. References 20, figures 5.